Construction, occupation et déconstruction de la grange gallo-romaine du “Parc des Châteaux” à La Chaussée-Saint-Victor (Loir-et-Cher) - Grégory Poitevin; Stéphanie Bigot; Marie-Pierre Chambon; Philippe Gardère; Dorothée Lusson (Revue Archéologique du Centre de la France)
The Gallo-Roman site of the ZAC du “Parc des Châteaux” at La Chaussée-Saint-Victor (Loir-et-Cher), has been explored over an area of around 1,600 m2. The excavation carried out in 2015 have enabled us to retrace the chronological and architectural evolution of a barn in use between the 1st and 3rd centuries AD. The results shed new light on this landmark building in the Beauce region. The demolition phase of the structure provides valuable data on the economics of recycling building materials. The study of the roof tiles, derived from the demolition backfill, is part of the enrichment of the regional corpus.